Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig - Tejerina, D; García-Torres, S; Cabeza de Vaca, M; Vázquez, F M; Cava, R (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.
Keywords: antioxidant; fatty acids; Iberian pigs; Montanera

Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. - Tejerina, D; García-Torres, S; de Vaca, M Cabeza; Vázquez, F M; Cava, R (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).
Keywords: acorns; diet composition; Grass; Iberian pigs; meat; Montanera

Interannual variability and evolution during the montanera period of Holm oak (Quercus rotundifolia Lam.) acorns - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Cava, R.; Vázquez, F. M. (Spanish Journal of Agricultural Research, 2010)
Eighty-eight samples of Quercus rotundifolia acorns were analyzed during three consecutive years (2005/06, 2006/07 and 2007/08) to determine variations in their morphology, sanitary condition, and nutritional composition throughout the same period of montanera (free-range swine-raising system of SW Iberia) and between different years of study. Results showed that morphological characteristics remained constant throughout montanera season. Fungal damage increased, and Curculio sp. and Cydia sp. pests decreased over the course of the montanera season. Dry matter content decreased in both kernel and pericarp (P < 0.001), while the crude fiber and protein contents were not modified. The ash, nitrogen-free extract, and fat contents, however, were also affected by sampling date within a montanera season. With respect to the interannual variability, variations (P < 0.05) were observed in all the variables studied. It is therefore confirmed that there is variability in the sanitary condition and nutritional composition of acorns within the same montanera season and between different years of study. These could explain the differences in the chemical characteristics of Iberian pig tissues from animals raised in different montanera seasons, and even during the same montanera season.
Keywords: acorn sanitary condition; Dehesa; feeding; Iberian pigs; proximate composition

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M.; Morcuende, D.; Ramírez, R.; Ventanas, J.; Cava, R. (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
The following values have no corresponding Zotero field: accession-num: 22061520
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M; Morcuende, D; Ramírez, R; Ventanas, J; Cava, R (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs